Effects of a Nursing Process-Based Management Model for Colonoscopy in Outpatients - Junsiri, Sudarut; Apiruknapanond, Panta; Phaktoop, Maneerat (Journal of health and health management, 2026)
This quasi-experimental study employed a two-group pretest-posttest design and aimed to develop a management model for colonoscopy using the nursing process for outpatients. The population was divided into two groups: 1) outpatients scheduled for diagnostic colonoscopy, with sample size calculated using G*Power at a 95% confidence level, totaling 122 participants divided into control and experimental groups of 61 each, and 2) internal stakeholders involved in receiving outcomes from the outpatient endoscopy center. Two sets of research instruments were used, consisting of experimental instruments and data collection instruments with reliability coefficients of 0.95 and 0.92, respectively. Data were analyzed using percentages, means, and standard deviations, with Independent t-test and Paired t-test employed for statistical analysis. The research findings revealed that: 1) the efficiency and effectiveness of colonoscopy in the experimental group were significantly higher than the control group (p < .01); 2) external service users’ satisfaction after receiving services was significantly higher in the experimental group compared to the control group (p < .01); and 3) internal stakeholders’ satisfaction after implementing the developed model was significantly higher than before implementation (p < .01).